Projekt Ansitz Löwengang. - Lageder, Alois; Verzotti, Giorgio (Margreid : Alois Lageder - Ansitz Löwengang, 2001)
Airo, Mario ; Bartolini, Massimo ; Cattelan, Maurizio ; Fortuyn/O'Brien ; Grünfeld, Thomas ; Höller, Carsten ; Merrick, Thom ; Müller, Christian Philipp ; Mullican, Matt ; Spalletti, Ettore ; Stingel, Rudolf ; Trockel, Rosemarie ; West, Franz
biog. p. 113
Duits
Projekt Ansitz Löwengang, Alois Lageder - Ansitz Löwengang, Margreid (Bozen), 2001
boek